2008
DOI: 10.1007/s00784-008-0223-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of platelet-rich plasma in periodontal surgery—a prospective randomised double blind clinical trial

Abstract: The aim of this prospective controlled randomized clinical trial was to evaluate the additional effect of platelet-rich plasma (PRP) in attachment gain. Twenty-two patients showing contralateral intrabony defects were included. Defects were randomized to beta-TCP (Cerasorb) in combination with PRP (test) or alone (control). Probing pocket depth (PPD), clinical attachment level (CAL), and relative AL (RAL) were assessed at the first, initial, re-evaluation (or basis examinations) and 6 months after surgery. Def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 39 publications
2
71
0
1
Order By: Relevance
“…The length of clinical and radiographic follow-up after surgery ranged from 6 months to 10 years. The reported PPD reductions from baseline to last follow-up after surgery ranged from 0.5 [22] to 9.3 mm [19] (median across studies 4.1 mm), while CAL reductions ranged from 0.6 [23] to 8.2 mm [19] (median across studies 3.2 mm). Sixty-eight studies reported baseline and follow-up linear radiographic bone changes after surgery, ranging from overall bone gains of 0.2 [24] to 9.3 mm [19] (median across studies 3.3 mm).…”
Section: Synthesis Of Resultsmentioning
confidence: 98%
“…The length of clinical and radiographic follow-up after surgery ranged from 6 months to 10 years. The reported PPD reductions from baseline to last follow-up after surgery ranged from 0.5 [22] to 9.3 mm [19] (median across studies 4.1 mm), while CAL reductions ranged from 0.6 [23] to 8.2 mm [19] (median across studies 3.2 mm). Sixty-eight studies reported baseline and follow-up linear radiographic bone changes after surgery, ranging from overall bone gains of 0.2 [24] to 9.3 mm [19] (median across studies 3.3 mm).…”
Section: Synthesis Of Resultsmentioning
confidence: 98%
“…Out of these, 3 papers were further rejected for the following reasons: two studies did not provide a control group [13, 14] and one was not a fully RCT [15]. Two articles were rejected because they did not provide comprehensive data and/or standard deviations to be analysed [16, 17]. …”
Section: Resultsmentioning
confidence: 99%
“…But when the local conditions are not optimum, PRP gels alone are not strong enough to promote a clinical filling equivalent to the dense bone filling reached with a bone substitute [50]. Most of the randomized controlled clinical trials(RCTs) demonstrated that the addition of PRP to certain regenerative materials, doi: 10.7243/2050-1218-2-11 namely bioactive glass [51], b-TCP [52], BM and e-PTFE membranes [53], b-TCP and e-PTFE membranes [54], BM and collagen membranes [23] and BM and EMD [55], failed to confer statistically significant additive benefits in the therapy of periodontal intraosseous defects. However, according to other RCTs such adjunctive positive outcomes may result from other combinations of PRP, namely together with BM [28], DFDBA [56] and hydroxyapatite [22].…”
Section: Discussionmentioning
confidence: 99%